Alternative für Deutschland: rhetoric against migrants as a threat to democracy in Germany - Gołębiowska, Klaudia (Wydział Nauk Politycznych i Dziennikarstwa Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2023)
The field of this artice is the far-right populist AfD party in the context of anti-immigrant rhetoric. I intend to establish to what extent the anti-immigrant agenda and activity can pose a threat to democracy in Germany. The field of research is the ideological background of the AfD. I intend to show what the anti-immigrant arguments stem from and what their boundaries are. In conducting research I adopted the main hypothesis according to which: far-right and populist AfD displaying anti-immigrant rhetoric are increasingly going beyond the boundaries of free speech to extremisms that undermine the constitutional order in Germany. The AfD aims to destabilise the democratic landscape by, among other things, building support for anti-immigrant attitudes. Przedmiotem niniejszego artykułu jest skrajnie prawicowa populistyczna partia AfD w kontekście antyimigranckiej retoryki. Celem jest ustalenie w jakim stopniu antyimigrancki program i działalności mogą stanowić zagrożenie dla demokracji w Niemczech. Obszarem badań jest ideologiczne tło AfD. Zamierzam pokazać, z czego wynikają argumenty antyimigranckie oraz jakie są ich granice. Prowadząc badania przyjęłam główną hipotezę, zgodnie z którą: skrajnie prawicowa i populistyczna AfD prezentująca antyimigrancką retorykę coraz częściej wykracza poza granice wolności słowa w kierunku ekstremizmów podważających porządek konstytucyjny w Niemczech. AfD dąży do destabilizacji demokratycznego krajobrazu, między innymi poprzez budowanie poparcia dla postaw antyimigranckich
Alternatywa dla Niemiec: retoryka przeciwko migrantom jako zagrożenie dla demokracji w Niemczech
Keywords: Alternative für Deutschland; AfD; hate speech; immigrants; democracy; Alternatywa dla Niemiec; mowa nienawiści; imigranci; demokracja